THE EFFECTIVENESS OF THE ELECTION SUPERVISORY AGENCY'S AUTHORITY IN HANDLING MONEY POLITICS IN THE 2024 ELECTION AND ITS IMPLICATIONS FOR THE QUALITY OF DEMOCRACY - Mochamad Irfan Hadi Prayitno; Moh. Sigit Gunawan (Hukum Responsif, 2027)
Background.. The utilization of monetary influence remains a significant issue in the electoral process in Indonesia, as it threatens the foundations of honest, equitable, and principled democracy. The Election Supervisory Agency (Bawaslu), functioning as an electoral oversight body, has the power to prevent, monitor, address, and rectify electoral infractions, including monetary manipulation. Nonetheless, in practice, numerous impediments continue to affect the efficacy of this authority. Aims. This research aims to evaluate the nature of Bawaslu's jurisdiction in addressing money politics during the 2024 election, assess the efficacy of its execution, and investigate its consequences for democratic standards in Indonesia. Methods. This research employs an empirical legal methodology (socio-legal inquiry) via a case study technique. Information was obtained from literature reviews of statutes and regulations, as well as official records, and corroborated by empirical data collected through interviews with Bawaslu. The examination is conducted qualitatively by correlating relevant legislative statutes with practical evidence concerning the management of monetary political practices in the 2024 election. Result. The findings of the research indicate that Bawaslu's jurisdiction is an attribution authority conferred directly by Law Number 7 of 2017, encompassing preventive, supervisory, administrative, coordinating, and advisory powers. The standard execution of this authority aligns with legal stipulations; however, its efficacy remains subpar due to insufficient evidence, minimal public engagement in reporting infractions, a transactional political environment, and the restricted jurisdiction of Bawaslu in the investigative and prosecutorial phases, which fall under the purview of the Integrated Law Enforcement Center (Gakkumdu Center). Conclusion. These conditions have an impact on the quality of democracy, especially in lowering the integrity of elections, freedom of choice, legitimacy of election results, and accountability in the administration of government. Implementation. Therefore, it is necessary to strengthen the authority of Bawaslu, increase coordination between law enforcement agencies, and increase public legal awareness in order to realize honest, fair, and integrity elections